2012
DOI: 10.1108/00483481211229366
|View full text |Cite
|
Sign up to set email alerts
|

Work‐based competences and careers prospects: a study of Spanish employees

Abstract: PurposeThis paper aims to identify the work‐based competences associated with better career prospects in the Spanish labour market.Design/methodology/approachThe relationship between employee‐based competencies and employment prospects is investigated through the lens of the competence‐based approach. The partial least squares (PLS) methodology is applied on a sample of over 5,000 Spanish employees.FindingsThe analysis establishes that skill, motivation, participation in decision‐making and the performance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 53 publications
0
23
0
1
Order By: Relevance
“…These behavioral requirements reflect and foster norms of hard interdependence. For instance, workers are often socialized through workplace interactions to value social relations, coworkers, and security (Cooke & Rousseau 1998, Friedlander 1965, Lamont 2000, Salzinger 2003, Urtasun & Núñez 2012. For example, Barker (1993) finds that both supervisors and coworkers in a working-class manufacturing company emphasize that job success relies on cooperating with fellow workers and being responsive to social norms.…”
Section: The Role Of the Workplacementioning
confidence: 99%
See 2 more Smart Citations
“…These behavioral requirements reflect and foster norms of hard interdependence. For instance, workers are often socialized through workplace interactions to value social relations, coworkers, and security (Cooke & Rousseau 1998, Friedlander 1965, Lamont 2000, Salzinger 2003, Urtasun & Núñez 2012. For example, Barker (1993) finds that both supervisors and coworkers in a working-class manufacturing company emphasize that job success relies on cooperating with fellow workers and being responsive to social norms.…”
Section: The Role Of the Workplacementioning
confidence: 99%
“…These behavioral requirements further reflect and foster norms of expressive independence. For instance, workers are often socialized through workplace interactions to value independence and freedom (Bacon & Storey 1996, Cooke & Rousseau 1998, Friedlander 1965, Hyman 1994, Lamont 2000, Urtasun & Núñez 2012. For example, Sutton & Hargadon (1996) found that IDEO (a professional product-design firm) emphasizes to employees that job success relies on challenging and breaking rules, expressing personal views, and being independent thinkers.…”
Section: The Role Of the Workplacementioning
confidence: 99%
See 1 more Smart Citation
“…Schmidt, Pohler, et al, 2018;Yanadori & Kang, 2011), Europe (e.g. Benzinger, 2016;Ramirez & Fornerino, 2007;Urtasun & N uñez, 2012), Oceania (e.g. McKeown & Lindorff, 2011), and Asia (e.g.…”
Section: Empirical Validationsmentioning
confidence: 99%
“…Furthermore, these studies showed that some specific HRM practices were strategically designed to be different for various employee groups based on their HC. Such HRM practices included the retention strategy (Gardner, 2005), compensation (Gowan & Lepak, 2007;Hong & Honig, 2016;McDonnell et al, 2016), career management (De Vos & Urtasun & N uñez, 2012), pay and performance management systems (Ferner & Almond, 2013), organizational socialization tactics (Benzinger, 2016), skill development (Okay-Somerville & Scholarios, 2019), and training (Meli an-Gonz alez & Verano- Tacoronte, 2004;Vyas & Zhu, 2017).…”
Section: Empirical Validationsmentioning
confidence: 99%